A Studying the Relationship of the Sdministrators with the Community of Opportunity Expansion Schools according to Saṅgahavatthu 4 Nakhonpathom Primary Education Service Area Office 1: - - Faikhongngoen, Anucha; Metheevachatra, Anond; Thuenchang, Worrakrit (Mahachula Academic Journal, 2026)
Abstract The objectives of this research were: (1) to study the relationship conditions between school administrators and the community in educational opportunity expansion schools according to the Four Sangahavatthu principles, and (2) to opinions regarding the relationship between school administrators and the community, classified by personal status factors including gender, age, position, educational level, and work experience. This study employed quantitative research methods. The sample group consisted of 210 participants, selected using the Krejcie and Morgan table and simple random sampling. The research instrument was a questionnaire on the relationship conditions between administrators and the community in educational opportunity expansion schools based on the Four Sangahavatthu principles. The statistics used for data analysis included percentage, mean, standard deviation, and t-test or One-Way ANOVA. Results of the research: (1) The overall state of relationships between school administrators and the communities was at a high level. When considering individual aspects, Public Relations had the highest mean, followed by Community Services, while Receiving Support and Assistance had the lowest mean.(2) The comparison of relationships between school administrators and the communities based on the Four Sangahavatthu—classified by gender, age, experience, and position—showed no statistically significant differences at the .05 level. Therefore, the results did not support the established hypothesis Keywords: Relationship of the Sdministrators; Community; Opportunity Expansion Schools; The Four Sangahavatthu principles.